+0  
 
0
231
2
avatar

(4x-3/-x+9) = (-3/-2)

Please solve for x

Also it helps to write it out as fractions

Guest Aug 4, 2017
 #1
avatar+90088 
+1

 

I'm assuming this might be :

 

(4x-3)/ (-x+9) = (-3/-2)   

 

(4x - 3) / ( -x + 9)  =  3/2   multiply both sides by (-x + 9)

 

(4x - 3)  = (3/2)(-x + 9)      multiply both sides by 2 to get rid of the fraction

 

2(4x -3)  = 3(-x + 9)          simplify

 

8x - 6  = -3x + 27           subtract 27, 8x  from both sides

 

-33  = -11x                  divide both sides by -11

 

3  = x 

 

 

 

cool cool cool

CPhill  Aug 4, 2017
 #2
avatar
0

Thx m8 cool

Guest Aug 4, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.